Trust, Risk and Uncertainty - Watson, S. author. aut Link
XII, 275 p.
Keywords: The themes 'trust', 'risk ' and 'uncertainty' seem especially pertinent in the context of the post-9/11 world. This book brings together a range of new research with a focus on the 'risk society' debate and on the themes of 'trust', 'uncertainty' and 'ambivalence'. Where much of the work within these crucial debates in the social sciences has been theory-based and theory-driven, Trust, Risk and Uncertainty combines theoretical sophistication with empirical analysis and research in the fields of philosophy, education, social policy, government, health and social care, sociology, and media and cultural studies.